DEVELOPING AN INSTRUMENT FOR RELATIONAL UNDERSTANDING ABILITY TEST AND INTERVIEW GUIDELINES - Rezi Ariawan; Hayatun Nufus; Erdawati Nurdin; Sai'da Tamalla Ali Akbar (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2024)
The development of this research instrument aims to produce an instrument for assessing the ability of relational understanding in the matter of two-variable linear equations (PLDV). The form of the research being carried out is research and development (Research and Development) in order to produce products measuring students' relational understanding abilities. The research location is at SMPN 37 Pekanbaru in the even semester of the 2022/2023 academic year. The object of research is an instrument for assessing the ability of relational understanding in class VIII2. The instrument for collecting data uses an instrument validation sheet. Data analysis shows that the 10 item items developed have a very valid category with an average of 0.83 and a reliability level of 0.92 which is in the very good category. In terms of difficulty level, half of the test instrument questions are in the category of moderate difficulty level and in the differentiating power of the questions, there are 4 questions that are in the bad category. So, basically questions that are appropriate for use in research are numbers 1,3,5,8 and 9. For the validity of the interview instrument, they are in a fairly valid category with a score of 0.8667. Keywords: relational understanding, validity, judgment